Gaya Tari dalam Konteks Nilai Budaya: Studi Kasus Tari Piriang Sulueh Minangkabau - Asriati, Afifah - (Fakultas Ilmu Sosial Universitas Negeri Padang, 2013)
The purpose of this article is to reveal the dance style of Tari Piriang Sulueh in contextual terms or correlation between Tari Piriang Sulueh dance with the underlying cultural values. Specifically, it aims to reveal the cultural values that expressed in (1) dancer, (2) motion, (3) property, (4) floor pattern, (5) fashion, (6) accompaniment and (7) the venue, as the contextual style had owned by Suluah Nagari Pariangan dance. To achieve this goal, there had been used qualitative antropological approach to observe the dance and to explore its culture through literature, other research findings, and interviewing the dance stakeholders. The result of this study shows that this Tari Piriang Sulueh dance is heavy with their daily and heredity cultural values. Kata Kunci: Gaya Tari, Nilai Budaya, Tari Piriang Sulueh